Do dog-human bonds influence movements of free-ranging dogs in wilderness? - Saavedra-Aracena, Lorena; Grimm-Seyfarth, Annegret; Schuttler, Elke (My University, 2021)
Domestic dogs have a close and mutualistic relationship with humans. When unconfined, they usually stay close to the owner's home, but some undertake intensive forays in nature with negative impacts on wildlife. Predictors for such problematic dogs in previous research concentrated on dog characteristics and husbandry. Here we additionally explored which aspects of the dog-human bond influenced the movements of free-ranging village dogs in southern Chile. Using an interdisciplinary framework, we assessed the strength of this relationship through (i) attachment behaviours performed during the Strange Situation Procedure (SSP, dog's perception of the relationship) and (ii) the Monash Dog-Owner Relationship Scale questionnaire (MDORS, owner's perception) in 41 dog-owner dyads while remotely monitoring the dogs' movements using GPS tracking (n = 36394 locations). We found that 39 % of dogs had > 5 % of their locations in natural areas, but only three individuals exhibited overnight excursions. Home range size (1.8-4227 ha) and mean distances to the owner's home (0-28.4 km) varied greatly among individuals. Through generalized linear models we identified that dogs had larger home ranges, moved farther away from home or accessed nature more (i.e., they exhibited more intensive forays) when they explored more, greeted their owners intensively, and expressed more passive behaviours in the presence of their owners (SSP). However, the MDORS questionnaire was a poor predictor of home range, distance to home, and access to nature. When considering the dogs' background, older dogs, males, and dogs that got missing more frequently exhibited more intensive forays. Compared to SSP results in confined dogs, we suggest that owners of free-ranging dogs do not play an important role as an attachment figure. We conclude that the dog-owner bond indeed influences roaming behaviour in dogs. This highlights the necessity of wildlife management strategies considering the cultural context. In specific terms, we recommend to foster the knowledge of the importance of bonds between dogs and their owners in educational campaigns on responsible dog ownership, along with biological (age, sex) and behavioural characteristics (exploration, getting missing). That way, awareness campaigns can focus on owners of possible problematic dogs.
Keywords: behavioural ecology; canis familiaris; chile; monash dog owner relationship scale; strange situation procedure; wildlife management